Problem-solving, Numerical and Variational Thinking in Elementary School: A Review (2021)
Problem-solving and numerical and variational thinking are aspects of mathematical competence in which elementary school students often have difficulties. This paper analyzes the state of research around problem-solving and numerical and variational thinking in primary education. The research used the hermeneutic and documentary approaches. Fifty scientific articles fulfilled the proposed inclusion criteria. As a result, it is found that most studies have sought to apply the Polya method, use technological, manipulable, and playful materials, relate problems to context, use inquiry to promote understanding and teaching, study the role of reading comprehension, and delve into students’ strategies and emotions when solving problems.  The results show that is possible to facilitate the learning of problem solving and numerical and variational thinking if students are challenged to solve contextualized tasks autonomously, in playful environments, and supported with reading comprehension and emotional self-regulation skills.